GAMBARAN MENGGOSOK GIGI DAN KEBIASAAN MENGKONSUMSI MAKANAN KARIOGENIK PADA ANAK USIA SEKOLAH DI SDN 54 TAHIJA BANDA ACEH - Sufriani .; Ruhul Aflah (Journal of Syiah Kuala Dentistry Society, 2018)
Dental caries is one of the most common dental and oral helath problem in school-aged children due to lack of understanding and behavior of children in maintaining dental health such as how to toothbrushing and the habit of eating snacks such as sweets. Research purpose is to describe how to toothbrushing and the habit of eating cariogenic foods in scool-ages children especially on classII andIIIstudentsclass atEementary School 54 Tahija Banda Aceh in 2013. This research is descriptiveanalytic. Sample of research is 144 students with total sampling technique. Colleting data usingquestionnaires and observation guided for tooth brushing demonstration. The data are analysed usingdescriptive analysis method. Result of the research showed that some respondents have not correctway to tooth brushing that is much as 52,1% dan most respondents are in the high category to eatcariogenic foods that is much as 53,5%. Expected to the school and the parents to be able to guideand teaches children how to tooth brushing properly and to restrict the eating of cariogenic foods so asto maintain optimal dental health, through cooperation with health workersKeywords: Tooth brushing, food, cariogenik